Denaturing Gradient Gel Electrophoresis (DGGE) Analysis Indicating Increased Microbial Diversity in Landfill Area Near Conserved Wetland - M. B. Chakraborty, S. R. Patgiri, A. S. Rahman, A. Dasgupta and G. Pegu (Nature Environment and Pollution Technology, 2023)
The ecological balance of an ecosystem has a relation to its biodiversity. Although it has been established that biodiversity and ecological stability are related, generalization about the exact nature of this relation remains elusive and more so in microbial diversity. A growing volume of studies has indicated that anthropogenic activities impact biodiversity, but it is difficult to generalize the impact of anthropogenic activities on microbial diversity. Landfilling by municipal solid waste is one such activity where microbes play a major role, and leachates are released from the landfill, altering the soil’s physical and chemical nature. Change in factors like carbon source, pH, and toxicity of the soil is most likely to affect the indigenous microflora of the soil. The present study was undertaken to compare the microbial diversity of soil receiving landfill leachate with that of the soil not receiving any landfill leachate to assess the impact of the landfilling activity on microbial diversity. The landfill site selected for the study was that of Kamrup Metro District of Assam, located at Boragaon, near the Ramsar wetland called Deeporbeel. By using the Denaturing Gradient Gel Electrophoresis (DGGE) method, it has been found that the microbial diversity of the soil receiving leachate was higher than that of the soil not receiving any leachate from the landfill.